Attitude Values in university student - Chaher, Faiza; Belayour, Tahar (Journal of Human Sciences, 2022)
Through this study, we aim to learn the Attitude values of the university student according to the Milton Rokich Value Scale. On the basis of this, the main question of the study was: What are the student’s Attitude towards values according to the Milton Rokich Value Scale? The prescriptive curriculum was adopted in this study. The sample study was 50 students in the Department of Arab Literature. The Milton Rokich scale was also used as the main tool for the study through which its hypotheses were tested. The result was that: The university student’s to Attitude wards instrumental values have been central values compared to religious values. -The Attitude of the university student towards terminal moral values have been negative as values of responsibility, honesty and rationality.